2023
DOI: 10.36956/rwae.v4i3.880
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Farmer Producer Organizations on Price and Poverty Alleviation of Smallholder Dry Chillies Farmers in India

Abstract: This study investigates the impact of Farmer Producer Organizations (FPOs) on smallholder dry chilli farmers in Guntur district, Andhra Pradesh, with a focus on price realization and poverty alleviation. Two specific FPOs, Red Chilli Farmer Producer Organisation and Spoorthi Chilli Producers Company Ltd., from the Guntur district of Andhra Pradesh were chosen for the study based on their substantial business turnover and comprehensive backward and forward linkages to their farmer-members. The smallholder farme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…The study by Desai and Joshi [27] uses propensity-score matching analysis in Gujarat and concludes that the poorest members of FPOs benefited the most. Kumar et al [28] revealed that FPO membership was crucial for farmers to reduce the poverty incidence rate. Kumar [29] demonstrated that producer share in the consumer rupee was higher for the channels of FPCs than other channels.…”
Section: Studies On Fpos In Indiamentioning
confidence: 99%
“…The study by Desai and Joshi [27] uses propensity-score matching analysis in Gujarat and concludes that the poorest members of FPOs benefited the most. Kumar et al [28] revealed that FPO membership was crucial for farmers to reduce the poverty incidence rate. Kumar [29] demonstrated that producer share in the consumer rupee was higher for the channels of FPCs than other channels.…”
Section: Studies On Fpos In Indiamentioning
confidence: 99%
“…In India, in the year of 2021-22 Andhra Pradesh tops the list in dry chilli production of 4.17 lakh tonnes covered under 2.25 lakh ha with 1809 kg/ha productivity followed by Telangana, Madhya Pradesh, Karnataka and West Bengal (Ministry of Horticulture, GoI) [7,8,9]. The country's output accounts for 36.00% of the global production with almost 50 varieties totalling 13 million MT Ram Singh et al [10].…”
Section: Globallymentioning
confidence: 99%